Therapy Algorithms for the Diagnosis and Treatment of Patients with Early and Advanced Breast Cancer - Schneeweiss, Andreas; Bauerfeind, Ingo; Fehm, Tanja; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Wöckel, Achim; Müller, Volkmar (Breast care, 2020)
Background: In order to offer optimal treatment approaches based on available evidence, the Commission Breast of the Working Group Gynecologic Oncology (AGO) of the German Cancer Society developed therapy algorithms for eight complex treatment situations in primary and advanced breast cancer. Summary: Therapy algorithms for the following complex treatment situations are outlined in this paper: (neo)adjuvant therapy of human epidermal growth factor receptor 2 (HER2)-positive breast cancer; axillary surgery and neoadjuvant chemotherapy; adjuvant endocrine therapy in premenopausal patients; adjuvant endocrine therapy in postmenopausal patients; hormone receptor (HR)-positive/HER2-negative metastatic breast cancer: strategies; HR-positive/HER2-negative metastatic breast cancer: endocrine-based first-line treatment; HER2-positive metastatic breast cancer: first to third-line; metastatic triple-negative breast cancer. Key Messages: The therapy options shown in these algorithms are based on the current AGO recommendations updated in January 2020 but cannot represent all evidence-based treatment options. Prior therapies, performance status, comorbidities, patient preference, etc. must be taken into account for the actual treatment choice. Therefore, in individual cases, other evidence-based treatment options not listed here may also be appropriate and justified.
Online veröffentlicht: 2. November 2020
Gesehen am 23.05.2024